2023
DOI: 10.3390/plants12183280
|View full text |Cite
|
Sign up to set email alerts
|

Plant and Disease Recognition Based on PMF Pipeline Domain Adaptation Method: Using Bark Images as Meta-Dataset

Zhelin Cui,
Kanglong Li,
Chunyan Kang
et al.

Abstract: Efficient image recognition is important in crop and forest management. However, it faces many challenges, such as the large number of plant species and diseases, the variability of plant appearance, and the scarcity of labeled data for training. To address this issue, we modified a SOTA Cross-Domain Few-shot Learning (CDFSL) method based on prototypical networks and attention mechanisms. We employed attention mechanisms to perform feature extraction and prototype generation by focusing on the most relevant pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…No research has been found where disease classification is conducted on a self-collected dataset comprising more than 70 classes. However, the research by Cui et al [156] and Gomes et al [157] employs very interesting techniques that deserve mention. The same classification approach was utilized in a joint project with the Temiryazev Academy as part of the World-class Scientific Center "Agrotechnologies of the Future" [158].…”
Section: Mlit Activities Related To Artificial Intelligence In Agricu...mentioning
confidence: 99%
“…No research has been found where disease classification is conducted on a self-collected dataset comprising more than 70 classes. However, the research by Cui et al [156] and Gomes et al [157] employs very interesting techniques that deserve mention. The same classification approach was utilized in a joint project with the Temiryazev Academy as part of the World-class Scientific Center "Agrotechnologies of the Future" [158].…”
Section: Mlit Activities Related To Artificial Intelligence In Agricu...mentioning
confidence: 99%